Control del riesgo crediticio y la gestión financiera en las MYPES de la ciudad de Pucallpa 2024 - Lazo Apagueño, Janis Casandra (2024)
The objective of this final report is to determine the relationship between credit risk control and financial management in the MYPES of the city of Pucallpa 2024, where a basic method was used, a descriptive-correlational level with a non-experimental design, working with a sample. of 264 Mypes to whom a questionnaire was used to collect data. The results show that credit risk control is regular with 28%, since they sometimes make financial projections to ensure their payment capacity, evaluate production before requesting a loan, consider the level of leverage and its impact on the risks, implement controls to avoid adverse operational events and encourage communication between departments to manage credit risks. For its part, financial management is regular (27%), since commercial credits are used flexibly and financial projections are made to plan future income and expenses. Additionally, in the last 6 months, there has been profitability on some occasions. Determining that there is a strong positive relationship between the variables, demonstrated by a coefficient of Rho=0.850 and a significance of 0.000.